Evaluating the costs and cost-effectiveness of interventions for people with learning disabilities and behaviour that challenges: the need to improve the evidence base. Issue 4 (3rd October 2016) - Hunter, Rachael
Abstract : Purpose: The purpose of this paper is to provide a commentary on the challenges associated with evaluating the costs and cost-effectiveness of interventions for people with learning disabilities and behaviour that challenges. Design/methodology/approach: The paper is a commentary on a range of evidence relating to the findings of "Positive behavioural support for children and adolescents with learning disabilities: an initial exploration of service and costs". Specific attention is paid to gaps in the literature and the evidence base for the cost of care for people with learning disabilities and behaviour that challenges. Findings: Recommendations for person-centred support and increased use of behavioural and psychological interventions for people with learning disabilities and behaviour that challenges are based on limited evidence. The literature is particularly sparse in relation to the cost implications for service providers or informal carers of implementing such interventions and the question of whether they reduce costs through preventing residential placements and long-term inpatient admissions. Originality/value: More high-quality research is required in the area of behavioural and psychological interventions for people with learning disabilities and behaviour that challenges. Trials in this area should include high-quality economic evaluations including budget impact analysis to provide information on the cost implications for different government agencies and cost-effectiveness analysis incorporating impact on quality of life.